Comparative toxicity of synchrotron and conventional radiation therapy based on total and partial body irradiation in a murine model - Lloyd M. L. Smyth; Jacqueline F. Donoghue; Jessica Ventura; Jayde Livingstone; Tracy E. Bailey; Liam Day; J. Crosbie; Peter A. W. Rogers (2018)
Synchrotron radiation can facilitate novel radiation therapy modalities such as microbeam radiation therapy (MRT) and high dose-rate synchrotron broad-beam radiation therapy (SBBR). Both of these modalities have unique physical properties that could be exploited for an improved therapeutic effect. While pre-clinical studies report promising normal tissue sparing phenomena, systematic toxicity data are still required. Our objective was to characterise the toxicity of SBBR and MRT and to calculate equivalent doses of conventional radiation therapy (CRT). A dose-escalation study was performed on C57BLJ/6 mice using total body and partial body irradiations. Dose-response curves and TD50 values were subsequently calculated using PROBIT analysis. For SBBR at dose-rates of 37 to 41 Gy/s, we found no evidence of a normal tissue sparing effect relative to CRT. Our findings also show that the MRT valley dose, rather than the peak dose, best correlates with CRT doses for acute toxicity. Importantly, longer-term weight tracking of irradiated animals revealed more pronounced growth impairment following MRT compared to both SBBR and CRT. Overall, this study provides the first in vivo dose-equivalence data between MRT, SBBR and CRT and presents systematic toxicity data for a range of organs that can be used as a reference point for future pre-clinical work.